Determination of the Standardized Ileal Amino Acid Digestibility of U.S. Tannin-Free Sorghum in Broilers - Santiago Sasia; William Bridges; Mireille Arguelles-Ramos (Agriculture)
This study aimed to assess the standardized ileal amino acid (AA) digestibility (SIAD) values in broilers (3 weeks of age) for tannin-free sorghum samples collected from the Southeastern region of the USA as well as provide a general comparison between sorghum vs. corn. An incomplete block design was implemented using the direct method to assess the SIAD of eight sorghum samples and one corn sample as the standard. Three of these sorghum samples were obtained from North Carolina (NC-PL, NC-T2, NC-LW), four samples from South Carolina (SC-Flo, SC-Pei, SC-Tub, SC-Experience), and one from Georgia (GA-Gf). Each tested grain was assigned to eight cages, with thirteen birds/cage. Birds were reared for 3 wks using the last 4 d as the experimental phase when ileal digesta were collected for SIAD assessment. Each sorghum sample’s digestibility was compared to that of corn. Generally, the South Carolina sorghum varieties showed the lowest AA digestibility values, except for SC-Flo, which had the highest digestibility, surpassing corn in Lys, Thr, Gly, and Asp (p < 0.05). Then, the sorghums’ SIAD values were pulled together for a general comparison to corn. Overall, the sorghum SIAD was comparable to corn (p > 0.05), but variations were noted among the AAs. Sorghum had better digestibility for Lys, Thr, and Asp while corn had more digestible Met, Leu, Pro, and Phe (p < 0.05). By integrating the crude protein content with SIAD data, this study provides an updated assessment of tannin-free sorghum’s protein quality. The findings suggest that tannin-free sorghum could serve as a practical alternative to corn in poultry feed, providing a comparable nutritional profile.